2001
DOI: 10.3390/60600519
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaromatization with 4-Hydroxycoumarin Part II: Synthesis of Some New Pyrano[2,3-d]pyrimidines, [1,2,4]triazolo[1,5-c]pyrimidines and Pyrimido[1,6-b]-[1,2,4]triazine Derivatives

Abstract: A variety of novel [1,2,4]triazolo[1,5-c]pyrimidine-13-ones (4a-f) and (5b-d) could be obtained via reaction of 9-amino-7-(4’-chlorophenyl)-8,9-dihydro-8-imino-6H,7H-[1]benzopyrano[3`,4`:5,6]pyrano[2,3-d]pyrimidine-6-one (3) with a variety of reagents. Pyrano[2,3-d]pyrimidine-6-ones 5a, 8a-c and pyrimido[1,6-b][1,2,4]-triazine-3,14-dione (6) were also prepared. The antimicrobial activity of some of the synthesized compounds was tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(60 citation statements)
references
References 5 publications
0
60
0
Order By: Relevance
“…Our research group has reported synthesis and application of some novel heterogeneous catalysts such as silica tungstic acid [13], silica-supported zirconium oxychloride (ZrOCl 2 .8H 2 O/SiO 2 ) [14], molybdate sulfuric acid [15], and tungstate sulfuric acid [16]. Recently, we have introduced SSC as a reusable silicasupported base catalyst [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has reported synthesis and application of some novel heterogeneous catalysts such as silica tungstic acid [13], silica-supported zirconium oxychloride (ZrOCl 2 .8H 2 O/SiO 2 ) [14], molybdate sulfuric acid [15], and tungstate sulfuric acid [16]. Recently, we have introduced SSC as a reusable silicasupported base catalyst [6].…”
Section: Resultsmentioning
confidence: 99%
“…Pyrano [2,3-h]coumarins as fused dihydropyrans with coumarin nucleus have been shown various pharmacological activities such as anti-HIV, antitumor, anticancer, antibacterial, and anti-inflammatory properties [9][10][11][12]. They are also valuable synthons for the synthesis of many pharmacological agents [13]. Furthermore, pyrano [2,3-h]coumarin derivatives have been applied as the main intermediate for the synthesis of thioxoimidazolidinedione, dithioxodiazetidine, and Schiff's bases [14].…”
Section: Introductionmentioning
confidence: 99%
“…The promising results of previous studies [18,23,45] prompted us to further extend our research towards the synthesis of annulation of heterocyclic systems of potential biological application. In continuation of our previous work we are reporting here the synthesis of some more analogues of benzochromene moiety as a base unit and antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover azo compounds are known for their antineoplastics [13], antidiabetics [14], antiseptics [15], antibacterial [16] and antitumor [17]. Benzochromene represent a class of heterocyclic compounds endowed with potent antimicrobial agents [18][19][20][21][22][23], antileishmanial [24,25], anticancer [26,27], antiproliferative [28], antioxidant [29,30], hypertensive [31], antitumor [32][33][34][35] effects and activities, as well as for the treatment of Alzheimer's disease [36], schizophrenia disorders [37], and fused chromene ring systems also displayed blood platelet antiaggregating [38], antihistaminic [39], analgesic [40][41][42], hypolipidemic [43], DNA breaking and mutagenicity activities [44].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, azo compounds are known for their antineoplastics [13], antidiabetics [14], antiseptics [15], antibacterial [16] and antitumor activities [17]. 4H-Pyran nucleus is a fertile source of biologically important molecules possessing a wide spectrum of biological and pharmacological activities such as antimicrobial [18][19][20][21], inhibitors of influenza virus sialidases [22,23], DNA strand-breaking activity and mutagenicity [24], antiviral agent [25], antiproliferation agent [26], sex pheromone [27], antitumor [28,29] and central nervous system (CNS) activity [18][19][20][21][22][23][24][25][26][27][28][29][30]. The synthesis of 4H-naphthopyrans involves a one-pot three-component coupling reaction of, p-chlorobenzaldehyde, malononitrile or ethyl cyanoacetate and phenyldiazenyl-1-naphthol.…”
Section: Introductionmentioning
confidence: 99%